The impact of different types of physical activity on total and regional bone mineral density in young Brazilian athletes - Silva, Carla C.; Goldberg, Tamara Beres Lederer [UNESP]; Teixeira, Altamir Santos [UNESP]; Dalmas, Jose C. (Taylor & Francis Ltd, 2011)
Bone turnover is affected by exercise throughout the lifespan, especially during childhood and adolescence. The objective of this study was to investigate the impact of different sports on total and regional bone mineral density in male Brazilian adolescent athletes. Forty-six adolescents aged 10-18 years participated in the study: 12 swimmers, 10 tennis players, 10soccer players, and 14 sedentary individuals. The athletes had engaged in physical activities for more than 10h per week in the previous 6 months. Bone mineral density of the lumbar spine (L1-L4), left proximal femur region, and whole body was evaluated by dual-energy X-ray absorptiometry. Results showed higher mean values in the proximal femur region of tennis and soccer players (1.02 +/- 0.18; 0.96 +/- 0.16, respectively) than swimmers and controls (0.91 +/- 0.14 and 0.87 +/- 0.06, respectively) (P0.05). In relation to the impact of sporting activities based on bone age determination, we observed significant differences in bone mineral density at all evaluated sites at the end of puberty (16-18 years) compared with 10-12 years, with increases of 78% in the lumbar spine, 47% in the proximal femur, and 38% in the whole body.
Keywords: Bone mineral density; adolescents; mechanical stress; exercise